A Red List of mites from the suborder Uropodina (Acari: Parasitiformes) in Poland - Napierała, Agnieszka (Exp Appl Acarol, 2018)
This article presents a Red List of mite species from the suborder Uropodina (Acari: Parasitiformes) occurring in Poland. Evaluation of the conservation status of the analyzed species was compiled on the basis of new criteria, which may also be applied to other groups of soil fauna. The authors employ the names of categories proposed by the International Union for Conservation of Nature (IUCN). One of our aims was to review the IUCN criteria to ascertain whether they are applicable in an attempt to assess the danger of extinction of soil invertebrates, and to see whether the criteria can be adapted to make such an assessment. The analyzed material contained 93 mite species obtained from 16,921 soil samples, which were collected between 1961 and 2017 in the whole area of Poland. The categories were assigned to species on the basis of the frequency of the species, but also other factors were taken into account, such as microhabitat specificity, vulnerability to detrimental conditions, and shrinking of local populations. One of the analyzed species can now be regarded as extinct, over 25% of the species (26 spp.) were labeled as critically endangered, and most of them (33 spp.) were categorized as vulnerable—the other species were assigned to the categories endangered (13 spp.), near threatened (10 spp.), and least concern (10 spp.).